Single and Synergistic Effects of Solar Radiation, Water guard and Moringa oleifera Treatments on Bacterial Loads and Physicochemical Parameters of Surface Water in Umur and Bele Streams of Benue State - Gberikon, G.M.; Adeoti, I.I.; Ogbonna, I.O. (International Journal of Applied Sciences and Biotechnology, 2018)
Bacteriological profiles of surface water samples treated with solar radiation, Moringa oleifera powder and water guard was carried out to ascertain their effectiveness in water treatment. Bacterial loads of the surface water collected from Umur and Bele streams in Gwer East Local Government area samples were determined before and after treatments and characterised using biochemical and molecular methods. Single and synergistic effects of these treatments on water quality were also examined. Bacteriological analysis showed that Umur stream had the highest bacterial loads of 4.47 x 103 cfu/mL while Bele had the lowest counts. There was significant reduction in the mean viable counts recorded for all the water samples (p ˂ 0.05). In the daily bacteria counts, the control water samples gave extremes values. There were no bacteria count recorded following combine treatment in water samples from Bele stream on the fifth day. Molecular analysis based on the 16S rRNA gene sequence showed bacterial strains to be phylogenetically close to bacterial strains which are capable of causing infectious diseases to man. Normal pH values were recorded in Umur stream while low pH values were recorded in Bele streams. Treatment impacted significantly on the pH of the water samples from Umur stream (p ˂ 0.05) while no significant difference was observed with water samples from Bele stream (p > 0.05). Treatment impacted significantly on turbidity in water sample from Umur stream (p ˂ 0.05). Sulphate was found to be within the permissible limit except for water sample from Bele stream which gave mean values within the range of 51.00 to 68.00 mg/L. Treatments impacted no significant difference on sulphate (p > 0.05). Surface water in these rural areas should be thoroughly treated before use. Int. J. Appl. Sci. Biotechnol. Vol 6(3): 244-251